2014
DOI: 10.1128/genomea.00016-14
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Genome Shotgun Sequence of Bacillus amyloliquefaciens Strain UASWS BA1, a Bacterium Antagonistic to Plant Pathogenic Fungi

Abstract: We report here the whole-genome shotgun sequence of Bacillus amyloliquefaciens strain UASWS BA1, isolated from inner wood tissues of a decaying Platanus × acerifolia tree. This strain proved to be antagonistic to several plant pathogenic fungi and oomycetes and can be developed as a biological control agent in agriculture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The genome size of B. amyloliquefaciens (UASWS BA1), an antifungal strain isolated from sycamore tree tissues, was found to be 3.944 Mb, with a GC content of 46.6%. Consistent with our results, previous research revealed that plant growth-promoting B. amyloliquefaciens includes subspecies with highly varied whole-genome sequence sizes, ranging from 3.86 to 4.24 Mb, with GC contents ranging from 45.7 to 46.6 percent [51]. The sequencing results of the current study are similar to those of the previous investigation, in which the genome of B. aryabhattai (SQU-R12) isolated from date palm saplings was found to be 5.584 Mb in size and to have a GC content of 37.74% [52].…”
Section: Discussionsupporting
confidence: 93%
“…The genome size of B. amyloliquefaciens (UASWS BA1), an antifungal strain isolated from sycamore tree tissues, was found to be 3.944 Mb, with a GC content of 46.6%. Consistent with our results, previous research revealed that plant growth-promoting B. amyloliquefaciens includes subspecies with highly varied whole-genome sequence sizes, ranging from 3.86 to 4.24 Mb, with GC contents ranging from 45.7 to 46.6 percent [51]. The sequencing results of the current study are similar to those of the previous investigation, in which the genome of B. aryabhattai (SQU-R12) isolated from date palm saplings was found to be 5.584 Mb in size and to have a GC content of 37.74% [52].…”
Section: Discussionsupporting
confidence: 93%
“…A second phylogenomic analysis was conducted using the core genome of all published or released B. siamensis (Jeong et al ., 2012), B. methylotrophicus and B. amyloliquefaciens genomes (Blom et al ., 2012; Cai et al ., 2014; Dunlap et al ., 2013; Geng et al ., 2011; Hao et al ., 2012; Lefort et al ., 2014; Manzoor et al ., 2013; Nelson et al ., 2014; Niazi et al ., 2014a, b; Yang et al ., 2011; Zhang et al ., 2011, 2014). The core genome for the group was 2948 genes.…”
Section: Resultsmentioning
confidence: 99%
“…plantarum strains as biological control agents and plant growth promoters (Ongena & Jacques, 2008; Pérez-García et al ., 2011; Shan et al ., 2013; Sharma & Satyanarayana, 2013; Shi et al ., 2014). In recent years, interest in understanding the mode of action of these strains has led to many genomes being published for these strains (Blom et al ., 2012; Cai et al ., 2014; Dunlap et al ., 2013; Geng et al ., 2011; Hao et al ., 2012; Lefort et al ., 2014; Manzoor et al ., 2013; Nelson et al ., 2014; Niazi et al ., 2014a, b; Yang et al ., 2011; Zhang et al ., 2011, 2014). At the time of writing, 28 genome assemblies had been reported for B. amyloliquefaciens and two had been reported for B. methylotrophicus.…”
Section: Introductionmentioning
confidence: 99%
“…Suspensions were made in 0.02% Tween 20 in ultrapure water (Siemens, Switzerland) and then spread on PGA medium at different dilutions to adjust the concentration of viable propagules at a final concentration of 10 7 cfu/ml. Bacterial aqueous suspensions were obtained from 2 day-old B. amyloliquefaciens strain UASWS BA1 (Lefort et al, 2014) grown in fresh Luria Bertani broth (LBB; Carl Roth, Switzerland) at room temperature in the dark under shaking at 150 rpm. Bacteria concentration of the liquid culture was first assessed with a Thoma haemocytometer.…”
Section: Biological Treatmentmentioning
confidence: 99%